Bioecology of An. philippinensis in Andaman group of Islands - M.K. Das, B.N. Nagpal, Aruna Srivastava & M.A. Ansari (Journal of Vector Borne Diseases, 2003)
Studies on bioecology of An. philippinensis a vector of malaria was carried out in eight islands of theAndaman group. It was found that An. philippinensis preferred to rest and bite outdoors. Maximumbiting was observed during 1800 to 2100 hrs on both cattle and human bait. The maximum breeding ofAn. philippinensis was recorded in slow moving stream followed by ponds with vegetation. Thebreeding sites infested with Chara and Spirogyra algae were most favourable whereas, with Lemnaand Oscillatoria were unfavourable for the proliferation of this species. The breeding association ofAn. philippinensis was found with other seven anopheline species in different breeding habitats.